Detection and serotyping of legionella pneumophila in faucets of selected intensive care units of a tertiary hospital in the Philippines - De Roxas, Dianne Melody A. (2017)
Hospital water systems are now considered as primary reservoir for nosocomial transmission of Legionnaires? disease, a fatal respiratory disease caused by Legionella spp. (Yu PY et al., 2007). In these settings, immunocompromised patients can be exposed to aerosols produced by aerosol-generating devices such as faucets, which facilitate the transmission of the bacterium. Thus, this study was conducted to determine the presence of Legionella pneumophila in faucets found in the Intensive Care Units of a tertiary hospital in Metro Manila. The study utilized a descriptive cross-sectional design where the proportion of the faucets positive for the bacterium was determined. Moreover, the species and serogroups of the isolates and the best conditions for the isolation of Legionella spp. Were identified in the study as well. A total of 18 faucets were tested for the presence of Legionella spp. From the four selected ICUs of a tertiary hospital. Bulk and swab samples were collected from each faucet. A combination of treatment methods and usage of two different culture media were employed in the methodology. The samples were concentrated, heat and acid treated and inoculated. Presumptive identification of the isolates as Legionella spp. Was done with cysteine dependence test and gram staining. Latex agglutination test, which utilized rabbit antibody sensitized latex particles reactive to L. pneumophila serogroup 1, 2-14 antigen, and antigens of the 9 commonly isolated Legionella species: L. micdadei, L. bozemanii 1 & 2, L. dumoffii, L.longbeachae 1 & 2, L. jordanis, L. gormanii, and L. anisa, was used for the identification pf the species and serogroups of Legionella isolates. The result of the study showed that 3 out of 18 faucets (16.67%) from two ICUs were positive for Legin ella spp. However, it was notable that no Legionella pneumophila was identified among the isolates, but were identified by the latex kit as Legionella species other than pneumophila. These findings showed that Legionella spp. Was present in the faucets of the ICUs and the potential of faucets as source of infectious aerosol that can be disseminated to the immunocompromised patients in the ICU. In addition, inclusion of Legionella detection as part of the control and monitoring measures in the infection and control program of the hospital should be taken into consideration.
Available in CD, pdf copy.
Thesis (Master of Science in Public Health (Medical Microbiology)--University of the Philippines Manila
Keywords: Legionella pneumophila; Legionella; Legionnaires' disease; Faucets